2016
DOI: 10.1177/1536012116683597
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Bone–Cartilage Interactions in Osteoarthritis Using [18F]-NaF PET-MRI

Abstract: Purpose:Simultaneous positron emission tomography–magnetic resonance imaging (PET-MRI) is an emerging technology providing both anatomical and functional images without increasing the scan time. Compared to the traditional PET/computed tomography imaging, it also exposes the patient to significantly less radiation and provides better anatomical images as MRI provides superior soft tissue characterization. Using PET-MRI, we aim to study interactions between cartilage composition and bone function simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…(37,38) Involvement of Dot1l in this process remains to be explored. In addition, in human osteoarthritis, cartilage degenerative changes are associated with increased turnover in the adjoining bone, but reduced turnover in the nonadjoining bone, (39) indicating interaction between cartilage integrity and surrounding bone.…”
Section: Discussionmentioning
confidence: 99%
“…(37,38) Involvement of Dot1l in this process remains to be explored. In addition, in human osteoarthritis, cartilage degenerative changes are associated with increased turnover in the adjoining bone, but reduced turnover in the nonadjoining bone, (39) indicating interaction between cartilage integrity and surrounding bone.…”
Section: Discussionmentioning
confidence: 99%
“…Current whole‐joint assessments of OA with MRI largely rely on semi‐quantitative scoring systems, which subjectively evaluate tissue structures . In a study of mild to moderate OA patients, increases in cartilage T 1ρ relaxation times, which are associated with a loss of cartilage GAG content, were correlated with increased 18 F‐NaF uptake in the adjoining bone as well as reduced uptake in the nonadjoining compartments . In a separate study of patients with unilateral, reconstructed ACL tears, a correlation was observed between increased 18 F‐NaF uptake measures of bone remodeling and increased T 2 values in adjacent cartilage, which is indicative of early collagen matrix breakdown .…”
Section: Applications Of Pet‐mri In Nononcologic Musculoskeletal Diseasementioning
confidence: 96%
“…Previous reports of high labelling efficiency and retention of [ 18 F]HFB over 4 h (77 - 95%) in vitro and in vivo [19,28] suggested the radiolabel may be well suited for monitoring individual cells in vivo using a trajectory reconstruction algorithm developed in-house [20,27]. In vitro bulk labelling of rat mesenchymal stem cells (MSCs) (5 × 10 5 /0.5 mL, 1 mCi, 30 min) indicated labelling efficiency of [ 18 F]HFB was 25% after 4h and [ 18 F]HFB-labelled cells were detected in the lungs 55-60 min post-intravenous injection [19].…”
Section: Discussionmentioning
confidence: 99%
“…While PEPT is used exclusively for studying chemical and industrial processes, the potential of PEPT for biomedical investigations, such as cell tracking, is increasingly being recognised [26]. To assess the feasibility of tracking a single cell, a novel trajectory reconstruction algorithm was developed in-house and validated using computer simulation and phantom models [20,27]. These simulations predict that labelling a single cell with 20 - 25 Bq (0.54-0.68 nCi) of activity is sufficient for tracking the cell in vivo using small animal PET.…”
Section: Introductionmentioning
confidence: 99%